MOLECULAR AND CELLULAR MECHANISMS OF ACTION OF SORBENTS USED IN MEDICINE - Rikhsi A. Sabirova; Aziza Kh. Aslanova (Central Asian Journal of Medicine, 2022)
The article provides an overview of the literature data on the effectiveness of the use of sorbents of various origins in diarrhea with various etiological causes. Enterosorbents, despite their very ancient use in medicine, are still relevant drugs. The use of this group of drugs has gone far beyond gastroenterology and makes it possible to effectively help patients with various diseases, including such "diseases of civilization" as cardiovascular pathology, disorders of lipid and carbohydrate metabolism. It is very valuable that the natural and safe composition of drugs, especially of domestic production, is also useful for healthy people in order to prevent diseases of the digestive system and prevent metabolic disorders: it allows achieving a higher quality of life - a priority task of medicine.